Factors Associated with Maternal Near Miss: A Study from Kerala - Reena R. P. and Radha K. R (Indian Journal of Public Health, 2018)
Severe life‐threatening situations leading to a “near‐miss” event may arise unexpectedly in pregnancy. Delay in seeking help, delayed access to care, and poor quality of emergency obstetric services can lead to undesirable outcomes. Women meeting the WHO “near‐miss” criteria were assessed using a cross‐sectional study design. These women were interviewed to evaluate the circumstances leading to a near‐miss event. Reasons for delays in getting proper care were studied using the “3 delays’ model.” Thirty‐two women met the criteria for “near miss” during the 15‐month study period, with a maternal near‐miss incidence ratio of 9.27/1000 live births. One or more delays were identified in 21 (65.6%) near‐miss cases. Delayed access to care was the most important factor for delay. A review of near‐miss cases can be used to improve and optimize the existing obstetric services.